Atomic scale switches based on solid state ionics. Issue 1 (31st December 2022) - Terabe, Kazuya; Tsuchiya, Takashi; Tsuruoka, Tohru
ABSTRACT: The atomic scale switch, which operates on the principle of solid-state ionics, is an ultrafine device that takes advantage of the fact that the properties of materials can be changed significantly by the transport and chemical reaction of a small number of ions in a solid. The switch (e.g. 'atomic switch') actually works by using an ion-conducting solid electrolyte or an ion-/electron-conducting mixed-conductor as the device material, and by applying an external voltage to control local ion transport and electrochemical reaction. With the application of an external voltage, a bridge is formed as a conductive filament in the solid electrolyte or the mixed conductor between electrodes. The atomic structure of the point contact in said filament can be reversibly changed by precise control of the applied voltage. By controlling the atomic structure of the point contact, interesting functions are obtained, such as fast on/off resistive switching, switching between each state of quantized conductance and neuromorphic properties. This atomic scale switch has the potential to overcome the functional and performance limitations of conventional integrated circuits because it can be used in conjunction with extant semiconductor devices. Graphical abstract: uf0001